84
$\begingroup$

I can't seem to find the answer to this using Google.

Is the transpose of the inverse of a square matrix the same as the inverse of the transpose of that same matrix?

$\endgroup$
  • 3
    $\begingroup$ This holds if the underlying ring is commutative as the answers show. If the underlying ring is not commutative, it might fail. $\endgroup$ – user44400 Jan 2 '17 at 16:52
  • $\begingroup$ By which you mean, if the entries in the matrices do not have the commutative property, then this does not necessarily hold? Interesting. Maybe you should add that, with a little more detail, to the existing accepted answer. $\endgroup$ – Void Star Jan 3 '17 at 16:53
  • 1
    $\begingroup$ @user44400: great observation! I noticed now for $2\times 2$ matrices over quaternions that we can have invertible matrices whose transpose is not invertible ( of course the conjugate transpose is...) $\endgroup$ – Orest Bucicovschi Mar 25 '18 at 9:26
142
$\begingroup$

Is $(A^{-1})^T = (A^T)^{-1}$ you ask.

Well $$\begin{align} A^T(A^{-1})^T = (A^{-1}A)^{T} = I^T = I \\ (A^{-1})^TA^T = (AA^{-1})^{T} = I^T = I \end{align} $$

This proves that the inverse of $A^T$ is $(A^{-1})^T$. So the answer to your question is yes.

Here I have used that $$ A^TB^T = (BA)^T. $$ And we have used that the inverse of a matrix $A$ is exactly (by definition) the matrix $B$ such that $AB = BA = I$.

$\endgroup$
  • $\begingroup$ So while below @haslersn equates (A−1)T=(AT)-1, you don't AT-1 in your proof at all. How does your conclusion follow? $\endgroup$ – atlex2 Dec 29 '18 at 19:31
  • $\begingroup$ @atlex2: I think you have misunderstood something. We are proving that $(A^T)^{-1} = (A^{-1})^T$. $\endgroup$ – Thomas Dec 30 '18 at 23:35
12
$\begingroup$

Suppose $A$ is an invertible square matrix. Then $A$ has a left-inverse; let us just call it $C$ to avoid confusing notation at first. So, $A$ being (left-)invertible means existence of some $C$ so that $$CA=I$$ Taking transposes on both sides and using the rule for transposing a product yields $$A^T C^T = I$$ The last equation shows that $A^T$ has a right-inverse (which is actually $C^T$), and so $A^T$ is (right-)invertible.

Do the analogous thing for the inverses from the other side, or appeal to the fact that for finite-dimensional matrices having an inverse from one side is enough to ensure that the same matrix is a two-sided inverse.

What we have then shown, is that $\left( A^T \right) ^{-1}$ exists and is given by the formula: $$\left( A^T \right) ^{-1} = \left( A^{-1} \right) ^T$$

This also shows, since the transpose of a transpose is the original matrix, that if $A$ is not invertible, then neither is $A^T$.

$\endgroup$
7
$\begingroup$

Given that $A\in \mathbb{R}^{n\times n}$ is invertible, $(A^{-1})^T = (A^T)^{-1}$ holds.

Proof:

$A$ is invertible and $\textrm{rank }A = n = \textrm{rank }A^T,$ so $A^T$ is invertible as well. Conclusion: $$(A^{-1})^T = (A^{-1})^TA^T(A^T)^{-1} = (AA^{-1})^T(A^T)^{-1} = \textrm{id}^T(A^T)^{-1} = (A^T)^{-1}.$$

$\endgroup$
  • $\begingroup$ Strong proof that connects (A−1)T=(AT)-1 in a one-liner. Nice. $\endgroup$ – atlex2 Dec 29 '18 at 19:31
4
$\begingroup$

I would derive the formula step by step this way.

Lets have invertible matrix A, so you can write following equation (definition of inverse matrix):

$AA^{-1} = I$

Lets transpose both sides of equation. (using $I^{T} = I$ , $(XY)^T = Y^TX^T$)

$(AA^{-1})^T = I^T$

$(A^{-1})^{T}A^T = I$

From the last equation we can say (based on the definition of inverse matrix) that $A^T$ is inverse of $(A^{-1})^{T}$. So we can write following.

$(A^{-1})^{T})^{-1}=A^T$

By inverting both sides of equation we obtain the desired formula.

$(A^{-1})^{T}=(A^T)^{-1}$

$\endgroup$
3
$\begingroup$

Well, if the underlying ring is not commutative, $(AB)^T = B^{T}A^T$ does not even hold for $1 \times 1$-matrices.

$\endgroup$
  • 3
    $\begingroup$ Someone had pointed out the same thing in a comment seven months ago. By the way, while what you say is technically true, what the OP asked for wasn't a proof of $(AB)^T=B^TA^T$, but $(A^{-1}))^T=(A^T)^{-1}$, and the latter equality does hold in the $1\times1$ case even when the ring is not commutative. $\endgroup$ – user1551 Aug 30 '17 at 0:01
2
$\begingroup$

Let the inverse of $A$ be $B^T$ so that $B$ is the transpose of the inverse of$A$. Then by definition of the inverse

$$AB^{T}=I=B^{T}A.$$

Now taking the transpose

$$BA^T=I=A^TB,$$

which proves that $B$ is also the inverse of the transpose of $A$.

$\endgroup$

protected by heropup Mar 25 '18 at 8:31

Thank you for your interest in this question. Because it has attracted low-quality or spam answers that had to be removed, posting an answer now requires 10 reputation on this site (the association bonus does not count).

Would you like to answer one of these unanswered questions instead?

Not the answer you're looking for? Browse other questions tagged or ask your own question.